THE ROLE OF THE PRINCIPAL AS A MANAGER IN ENHANCING TEACHER PROFESSIONALISM AT SD NEGERI 07 BANTARBOLANG PEMALANG REGENCY - Purwati Purwati; Sumarno Sumarno; Rasiman Rasiman (Program Studi PGSD Universitas Flores, 2025)
This study addresses the issue of low levels of teacher professionalism, which can hinder the quality of education in primary schools. The research aims to describe in depth the role of the principal as a manager in enhancing teacher professionalism at SD Negeri 07 Bantarbolang. A qualitative descriptive method was employed, with data collected through in-depth interviews, participatory observation, and document analysis. The results show that the principal actively plans, implements, and evaluates various programs to improve teacher professionalism. Specific strategies include academic supervision, internal training sessions, and the development of a collaborative work culture focused on strengthening teacher competencies. Data validity was ensured through triangulation of sources and methods, as well as member checks to enhance credibility. The study concludes that effective managerial leadership by the principal plays a significant role in improving teacher professionalism, thereby contributing positively to the overall quality of education.